English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Please answer and how.

2007-05-24 06:27:18 · 5 answers · asked by jredsje 2 in Science & Mathematics Mathematics

5 answers

2x² - 7x = - 3

2x² - 7x + 3 = - 3 + 3

2x² - 7x + 3 = 0

The middle term is - 7x

find the sum of the middle term

multiply the first tersm 2 times the last term 3 equals 6 and factor

factors of 6

1 x 6. . .<=. .Use these factors
2 x 6

- 6 and - 1 satisfy the sum of the middle term

- 1 = - x

insert - 6x and - x in to the equation

2x² - 7x + 3 = 0

2x² - 6x - x + 3 = 0

2x(x - 3) - 1(x - 3) = 0

(2x - 1)(x - 3)

- - - - - - - - - - -s-

2007-05-24 06:56:11 · answer #1 · answered by SAMUEL D 7 · 1 0

Bring 3 to the other side
2x^2-7x+3=0
x=3
x=1/2

2007-05-24 06:33:10 · answer #2 · answered by gartfield72 2 · 0 0

2x^2-7x= -3 add 3 to both sides
2x^2-7x+3=0 Now factor
(2x-1)(x-3)=0

2007-05-24 06:31:47 · answer #3 · answered by txmama423 3 · 0 0

2x² -7x = -3

2x² -7x + 3 = 0

(2x - 1)(x - 3) = 0

x = 1/2, x = 3
.

2007-05-24 06:31:49 · answer #4 · answered by Robert L 7 · 0 0

2x² - 7x + 3 = 0
(2x - 1)(x - 3) = 0

2x - 1 = 0, 2x = 1, x = 1/2 or
x - 3 = 0, x = 3

2007-05-24 06:31:29 · answer #5 · answered by Philo 7 · 0 0

fedest.com, questions and answers